A knowledge management framework to support product-service systems design - Baxter, David; Roy, Rajkumar; Doultsinou, Athanasia; Gao, James X.; Kalta, M. (Taylor & Francis, 2009)
This paper presents a framework for knowledge reuse in a Product-Service Systems design scenario. The project aim is to develop a methodology to capture, represent and reuse knowledge to support product development in a collaborative enterprise context. The three core elements are: design knowledge, manufacturing capability knowledge, and service knowledge. There are three principal components of the proposed methodology. The first is a process based design model: defining design according to specific tasks, and associating previous knowledge with those tasks. The second is manufacturing capability knowledge: supporting feature based design and manufacture through representing machining features, best practices in machining and inspection, and machining capability. The third component is service knowledge: ensuring that design takes account of the service requirement. The developing paradigm of Product-Service Systems and the requirement for co-design of products and services has influenced the structure of the knowledge base, as well as outlining specific service related requirements. This paper presents the proposed knowledge base structure along with a detailed case study in which the proposal was developed and validated.
Keywords: design; innovation management; product development; design for service; design for manufacture; knowledge management